Penerapan Flipped Classroom dalam Meningkatkan Maharatul Kalam Mahasiswa PBA UIN Sunan Kalijaga - Kusuma, Rani Kusumaningrum; Rodiah, Ita (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2025)
ABSTRACT This study aims to determine the effect of the application of flipped classroom in improving maharatul kalam of PBA UIN Sunan Kalijaga students. This research uses a descriptive qualitative approach using a questionnaire method. Students were asked to study the material independently outside the classroom, while the time in class was for discussion and practice of speaking Arabic actively. The result showed that the application flipped classroom can significantly improve students confidence and maharatul kalam in Arabic, although there are some challenges related to access to materials and motivation to learn independently. This study concludes that the flipped classroom method is effective for improving students maharatul kalm in Arabic.